2022
DOI: 10.52001/vis.2022.10.45.53
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine Propagation Method with Two Temperature Controlling Process

Abstract: Since vine propagation methods can cause physiological stress, it has a great impact on sustainable viticulture. The aim of this review is to introduce the applied techniques in decreasing the time period and manage the physiological stage of vine cuttings by simultaneously manipulating the temperature of two nodes of the same cuttings in order to stimulate roots and inhibit shoot formation for vegetative propagation. To avoid mold and other bacterial diseases, antifungal and antibacterial treatment is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…(1) in this I is a vine that goes through the vine, A; S is the cross-sectional surface of the grapevine, m2; Studies have shown that the processing time (τ) of alternating electric current flowing through the handle, the geometric dimensions of the handle depending on the physiological state (diameter (d), surface (S) and length of the handle (l), network voltage (U), distance between electrodes (l) and showed the dependence of the current supplied to the pen (f). In studies on the electrical processing of grapevine cuttings, various methods of placing the cuttings in the working chamber were tested [11,12]. These studies did not study the electrophysical processes when the sludge was not immersed in water, and the study of the current flow through the sludge per unit time for a given production line is a reason for understanding important factors.…”
Section: S I J mentioning
confidence: 99%
See 3 more Smart Citations
“…(1) in this I is a vine that goes through the vine, A; S is the cross-sectional surface of the grapevine, m2; Studies have shown that the processing time (τ) of alternating electric current flowing through the handle, the geometric dimensions of the handle depending on the physiological state (diameter (d), surface (S) and length of the handle (l), network voltage (U), distance between electrodes (l) and showed the dependence of the current supplied to the pen (f). In studies on the electrical processing of grapevine cuttings, various methods of placing the cuttings in the working chamber were tested [11,12]. These studies did not study the electrophysical processes when the sludge was not immersed in water, and the study of the current flow through the sludge per unit time for a given production line is a reason for understanding important factors.…”
Section: S I J mentioning
confidence: 99%
“…  (10) in this: W1 -useful energy absorbed by grapevine cuttings; W2 -energy used for electrical heating of water; In his studies, V.A. Petrukhin determined expression (11) during the electrical treatment of fruit tree cuttings, that is, he described the degree of susceptibility Sst during the electrical treatment of fruit tree cuttings as follows. (11) in this: S0 -initial resistance, %; γ=β/Rн -marking is on; β -proportionality coefficient, Ω /J; RT-current resistance, Ω; Rн -initial resistance, Ω αproportionality coefficient, 1/J.…”
Section: Fig 5 Scheme Of Supplying Grape Cuttings With Electricitymentioning
confidence: 99%
See 2 more Smart Citations